Для функции ((A∧B)→¬(A∧C))∨B:


Промежуточные таблицы истинности:
A∧B:
ABA∧B
000
010
100
111

A∧C:
ACA∧C
000
010
100
111

¬(A∧C):
ACA∧C¬(A∧C)
0001
0101
1001
1110

(A∧B)→(¬(A∧C)):
ABCA∧BA∧C¬(A∧C)(A∧B)→(¬(A∧C))
0000011
0010011
0100011
0110011
1000011
1010101
1101011
1111100

((A∧B)→(¬(A∧C)))∨B:
ABCA∧BA∧C¬(A∧C)(A∧B)→(¬(A∧C))((A∧B)→(¬(A∧C)))∨B
00000111
00100111
01000111
01100111
10000111
10101011
11010111
11111001

Общая таблица истинности:

ABCA∧BA∧C¬(A∧C)(A∧B)→(¬(A∧C))((A∧B)→¬(A∧C))∨B
00000111
00100111
01000111
01100111
10000111
10101011
11010111
11111001


Это интересно...

Наши контакты

Рейтинг@Mail.ru

© 2009-2018, Список Литературы